Identification of Lysine Histidine Transporter 2 as an 1-Aminocyclopropane Carboxylic Acid Transporter in Arabidopsis thaliana by Transgenic Complementation Approach - Choi, Jungki; Eom, Sanung; Shin, Kihye; Lee, Rin-A; Choi, Soobin; Lee, Jun-Ho; Lee, Sumin; Soh, Moon-Soo (Frontiers in Plant Science, 2019)
1-aminocyclopropane-1-carboxylic acid (ACC), a biosynthetic precursor of ethylene, has long been proposed to act as a mobile messenger in higher plants. However, little is known about the transport system of ACC. Recently, our genetic characterization of an ACC-resistant mutant with normal ethylene-sensitivity revealed that LYSINE HISTIDINE TRANSPORTER1 (LHT1) functions as a transporter of ACC. As amino acid transporters might have broad substrate specificity, we hypothesized that other amino acid transporters including LHT1 paralogs might have the ACC-transporter activity. Here, we took a gain-of-function approach by transgenic complementation of lht1 mutant with a selected set of amino acid transporters. When we introduced transgene into the lht1 mutant, the transgenic expression of LHT2, but not of LHT3 or AMINO ACID PERMEASE5 (AAP5), restored the ACC-resistance phenotype of the lht1 mutant. The result provides genetic evidence that some, if not all, amino acid transporters in Arabidopsis can function as ACC transporters. In support, when expressed in Xenopus laevis oocytes, both LHT1 and LHT2 exhibited ACC-transporting activity, inducing inward current upon addition of ACC. Interestingly, the transgenic expression of LHT2, but not of LHT3 or AAP5, could also suppress the early senescence phenotypes of the lht1 mutant. Taking together, we propose that plants have evolved a multitude of ACC transporters based on amino acid transporters, which would contribute to the differential distribution of ACC under various spatiotemporal contexts.